Relación entre Autoestima y Dependencia Emocional en Estudiantes de Psicología de Riohacha (2022)
In this research, an analysis was made of the relationship between the variables of self-esteem and emotional dependence in psychology students of the Antonio Nariño University in the city of Riohacha. To carry out the study, two instruments were applied: an Emotional Dependence Questionnaire (CDE) and the Rosenberg Self-Esteem Scale, where different dimensions were measured to identify the relationship. The analysis technique based on Cronbach's alpha was taken into account to obtain data accuracy. The results show that there is a significant relationship between both variables because they exceed the coefficient of 0.97, presenting a low and very low self-esteem that may result in a high level of emotional dependence in students. In conclusion, it is considered necessary to inquire about the direct effect that self-esteem has on emotional dependence in order to know the dimensions or factors that influence it.